Integrating circular economy and Industry 4.0 for sustainable supply chain management: a dynamic capability view - Guoqing Zhao (Production Planning and Control, 2022)
Circular economy (CE) and Industry 4.0 are recent business buzzwords that help organizations to maintain a circular flow and optimize the use of resources with technological supports to improve sustainability practice. Transition towards CE and Industry 4.0 is promising and yet challenging. As such, the aim of this research is to investigate how to integrate CE and Industry 4.0 in sustainable supply chain management (SSCM) in order to improve operational efficiency and sustainability performance. This study provides an analysis of the dynamic changes of drivers and barriers when integrating CE and Industry 4.0 and their related applications in operations and SCM through a systematic review of literature. From the results, a theoretical framework was derived for future research development.